Wavelength tunable tetraphenylethene fluorophore dyads: Synthesis, aggregation-induced emission and Cl2 gas detection. (February 2018) - Ma, Liangwei; Li, Chengpeng; Liang, Qiufeng; Wang, Sheng; Cao, Derong
Abstract: We designed and synthesized three new tetraphenylethene (TPE) derivatives (CZ-TPE, DMA-TPE andTPA-TPE ) modified with different electron rich group (carbazole, N, N -dimethylaniline and triphenylamine segments, respectively) by Knoevenagel condensation reaction. The chemical structures of these compounds are identified by NMR, MS and IR. The absorption and emission of these dyes were investigated by UV-Vis and fluorescence spectroscopy, respectively. The results shown three dyes exhibited evident aggregation-induced emission (AIE) or aggregation-induced emission enhancement (AIEE) properties with wavelength tunable emission. Their emission color can be tuned from green to orange in tetrahydrofuran/H2 O solutions, from green to red in solid state or pure tetrahydrofuran solutions. In addition, the solution or film ofTPA-TPE shown results in distinct fluorescence from "ON" to "Off" observation as well as color change from orange yellow to colorless by naked eyes when the addition of toxic Cl2 gas, which can be used as an excellent dual chromo- and fluorogenic signal changes that is well suited for monitoring Cl2 gas in solution, or solid film, conveniently. These results indicateTPA-TPE is a promising candidate chemosensor for the detection of Cl2 gas. Graphical abstract: Highlights: Three new emission color tunable AIE dyes have been designed and synthesized efficiently. TPA-TPE can work as an efficient dual signaling gas chemosensor for the detection of Cl2 gas. Sensor can be triggered by low concentration Cl2 whether in solution or solid state conveniently.